2021
DOI: 10.21203/rs.3.rs-253548/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircRNA Expression Patterns and circRNA-miRNA-mRNA Networks During CV-A16 Infection of SH-SY5Y Cells

Abstract: Coxsackievirus A16 (CV-A16) has caused worldwide epidemics of hand, foot, and mouth disease (HFMD), particularly among infants and preschool children. Circular RNAs (circRNAs) are a recently identified class of noncoding RNA molecules that participate in the occurrence and development of numerous infectious diseases. To date, the function of circRNAs has been a heavily researched topic, and their role in CV-A16 infection has not been fully elucidated. In this study, the viral effects of CV-A16 on the cellular … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…Enrichment analysis showed that enriched GO-BP terms mainly focused on the "metabolic process" and "protein modification," which was largely consistent with EV71 or CV-A16 virus infection. However, enrichment analysis of SH-SY5Y cells infected with EV71 or CA-16 indicated association with the "gonadotropin-releasing hormone receptor pathway," "Wnt signaling pathway," "angiogenesis," and "p53 pathway", which were not present in our analysis with CVB5 infection [24,25]. In our study, host genes that correspond to the differentially expressed circRNAs were mainly involved in "ubiquitin mediated proteolysis", "tight junction," and the regulation of other signaling pathways, such as the MAPK pathway.…”
Section: Discussioncontrasting
confidence: 68%
“…Enrichment analysis showed that enriched GO-BP terms mainly focused on the "metabolic process" and "protein modification," which was largely consistent with EV71 or CV-A16 virus infection. However, enrichment analysis of SH-SY5Y cells infected with EV71 or CA-16 indicated association with the "gonadotropin-releasing hormone receptor pathway," "Wnt signaling pathway," "angiogenesis," and "p53 pathway", which were not present in our analysis with CVB5 infection [24,25]. In our study, host genes that correspond to the differentially expressed circRNAs were mainly involved in "ubiquitin mediated proteolysis", "tight junction," and the regulation of other signaling pathways, such as the MAPK pathway.…”
Section: Discussioncontrasting
confidence: 68%